ANALISIS KOMPETENSI PROFESIONAL GURU BIOLOGI SMA DI KECAMATAN RAMBAH HILIR - Roskia, Dewita (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to determine the professional competence of high school biology teacher in District Rambah Hilir. This study uses descriptive research. The population in this study is a high school biology teacher in Rambah Hilir with numbered 5 people. Sampling using saturated sample that all members of the population sampled. Data collection techniques using triangulation techniques. The result showed an understanding of teaching materials in the curriculum with an average of 80.63%, understanding the structure, concepts and methods of science teaching materials that overshadow the assessed average of 80.00%, to understand the relationship between the concepts related subjects with 78, 00%, applying the concepts to everyday life with an average of 70.00% and mastering the steps of research and critical studies to deepen knowledge or subject material with an average of 70.00%. Of the overall results obtained an average of 76.33% with criteria quite well.Â